Pengaruh Kompetensi, Akuntabilitas Terhadap Penyusunan Anggaran Dengan Komitmen Organisasi Sebagai Variabel Moderating Pada SMA Swasta Bagian Medan Utara - Laila Fajrin Manik; Eka Nurmala Sari; Irfan (LPPM POLITEKNIK LP3I BANDUNG, 2022)
The purpose of this study was to examine and analyze the influence of competence on the budgeting of the North Medan Private High School. To test and analyze the effect of accountability on the budgeting of the North Medan Private High School. To test and analyze organizational commitment, competence can be moderated by preparing a budget for the North Medan Private High School. To test and analyze organizational commitment can moderate accountability with the preparation of the budget of the North Medan Private High School. This research uses a quantitative associative approach with data collection techniques through literature studies and questionnaires. The population of this research is a private high school in North Medan with a total of 90 teachers. The data analysis of this research used quantitative data analysis techniques. The statistic used is Structural Equation Model - Partial Least Square (SEM-PLS). Software to process this research data using SmartPLS. The results of the study indicate that competence has an effect on budgeting. Accountability affects the preparation of the budget. Organizational commitment can moderate the influence of competence on budgeting. Organizational commitment can moderate the effect of accountability on budgeting